Preliminary study on lactate production utilizing the turbidostat system - Ratna Sri Dewi, Binti Sedi (Universiti Malaysia Sarawak (UNIMAS), 2005)
The possibility of utilizing the Turbidostat System in lactic acid fermentation was investigated in this study. Hydrolysed sago starch (HSS) was used as a carbon source of glucose to produce lactic acid by Lactococcus lactis 101. Batch fermentation system was conducted at pH 6.0 maintained at 37°C. The highest concentration oflactic acid, 33.0 giL, was obtained at 24 hours fermentation and the turbidometer reading is 0.093. The biomass concentration and residual glucose is 2.35 gIL and 10.83 gIL respectively. Later, continuous fermentation was carried out with cell recycling using the same parameters as in batch fermentation and the flow rate of media is 50 mLlhour. The cell recycling was performed at 16 hours of fermentation. The lactate concentration and biomass concentration obtained during 24 hours of continuous fermentation was higher than in batch fermentation with 38.75 gIL and 3.44 gIL respectively. The turbidometer reading is 0.098. The highest lactate production was obtained at 48 hours of fermentation with the value 60.18 giL and turbidometer reading is 0.28. The biomass concentration and residual glucose concentration is 13.9 giL and 13.81 giL respectively.